2019
DOI: 10.7717/peerj.7242
|View full text |Cite
|
Sign up to set email alerts
|

RAD genotyping reveals fine-scale population structure and provides evidence for adaptive divergence in a commercially important fish from the northwestern Pacific Ocean

Abstract: Exploring factors shaping genetic structure of marine fish is challenging due to fewer barriers to gene flow in the ocean. However, genome-wide sequence data can greatly enhance our ability to delineate previously unidentified population structure as well as potential adaptive divergence. The small yellow croaker (Larimichthys polyactis) is a commercially important fish species with high gene flow and its overwintering populations experience heterogeneous environment, suggesting possible population differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 78 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…Mutations in genes associated with the immune response may provide evidence of resistance specificity to temperature stress in different geographic populations (Additional file 1 ). For example, the immune response was shown to be related to local adaptation to different water temperatures in Tylosurus crocodilus crocodilus [ 23 ], Trachidermus fasciatus [ 13 ], and Larimichthys polyactis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in genes associated with the immune response may provide evidence of resistance specificity to temperature stress in different geographic populations (Additional file 1 ). For example, the immune response was shown to be related to local adaptation to different water temperatures in Tylosurus crocodilus crocodilus [ 23 ], Trachidermus fasciatus [ 13 ], and Larimichthys polyactis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies on fish morphology and spawning migration routes, three populations are distinguished: the East China Sea, the southern Yellow Sea, and the Bohai/northern Yellow Sea populations (Lin, 1987;Liu, 1990). With the introduction of various methods of population division analysis, such as evaluation of otolith morphology and microchemistry (Zhang et al, 2014;Wang et al, 2016), morphometric characteristics (Zhang et al, 2015), and population genomics (Zhang B. D. et al, 2019), an increasing number of cryptic populations have been reported. In addition to an unrecognized L. polyactis cryptic population, its spawning grounds also should also be considered in the design of management strategies.…”
Section: Connectivity Between Overwintering and Spawning Groundsmentioning
confidence: 99%
“…Transboundary overwintering migratory habits limit the investigation and assessment of the overwintering grounds of SYS (Liu et al ., 2020), resulting in a lack of understanding of suitable habitat distribution for the overwintering stock. Overwintering migration of L. polyactis is an essential component of its population dynamics and is closely related to elements of the marine environment, such as sea bottom temperature (SBT), sea bottom salinity (SBS), chlorophyll‐a concentration (Chla) and water depth (Depth) (Liu et al ., 2020; Tang et al ., 2018; Zhang et al ., 2019). Recruitment and surplus require a suitable marine environment for overwintering, which is the determining factor for the rise and fall of L. polyactis resources.…”
Section: Introductionmentioning
confidence: 99%